Proteomic analysis of the cytotoxic effects induced by the organogold(iii) complex Aubipyc in cisplatin-resistant A2780 ovarian cancer cells: further evidence for the glycolytic pathway implication12. Issue 6 (19th June 2015) - Gamberi, Tania; Magherini, Francesca; Fiaschi, Tania; Landini, Ida; Massai, Lara; Valocchia, Elisa; Bianchi, Laura; Bini, Luca; Gabbiani, Chiara; Nobili, Stefania; Mini, Enrico; Messori, Luigi; et al.
<x xml:space="preserve">Abstract</x> The cytotoxic mechanisms of the organogold(iii) Aubipyc.